Engaging faith-based communities in pro-environmental behavior using soft regulations: The case of single-use plastics - Kaufmann, Dan; Tikotsky, Ariel; Yoreh, Tanhum; Tchetchik, Anat (Frontiers in Environmental Science, 2023)
ABSTRACT The consumption of single-use plastics, such as disposable tableware (DTW), conveys a high benefit-cost ratio for consumers while having large environmental externalities. To encourage consumers to reduce their usage of DTWs, governments could employ small and non-coercive changes in people’s decision-making environments (nudges). This study focuses on the Israeli Ultra-Orthodox community, a secluded population group that grows much faster- and consumes much more DTW compared to the rest of the Israeli population. Employing a quasi-representative sample (N = 450) of this population, this study conducted a discrete-choice experiment conducted that presents the respondent with alternative options to reduce DTW. Two kinds of Nudges –framing and social norms – were utilized. The effectiveness of these Nudges in promoting PEB among faith-based communities received little attention in previous studies. As another contribution to the literature, this paper also integrates latent constructs such as the respondents’ environmental attitudes and level of conservativeness. 46% of the respondents chose to opt-out whereas 29%, 14%, and 11% chose ‘one-day’, ‘two-days’, and ‘three-days’ per week avoiding DTW, respectively. Social norms, framings, and environmental attitudes had a significant mediating effect, with framing being associated with the highest effect on intentions to reduce DTW, i.e., a willingness to give up 0.31 USD per family member per month, compared to 0.07 USD for an increase in the description of the social norm. The results suggest that Nudges can enhance policies aimed at encouraging pro-environmental behavior among faith-based communities.